Spending behavior trends among Academy of Contemporary Islamic Studies Students in UiTM Puncak Alam / Muhammad Zainul Muttaqin Mohd Jasli. - Mohd Jasli, Muhammad Zainul Muttaqin (2019)
Spending behavior is behavior that will not be excluded by any students in the univer-sity. It is because the spending behavior is a general habit that influenced the students during their studies. The differential between the students in spending behavior is only their awareness. The sources of money that they gained also influenced their behavior of spending. The objectives of this research are to evaluate the spending amount, spend-ing method and also spending priority during studies among IC1105C students in UiTM Puncak Alam. This research was used the quantitative method which using the ques-tionnaire survey in order to get the information from respondents. 35 out of 37 students were involved and answered the questionnaire that contributed. The data received also was generated by SPSS software since this research used the descriptive method. This research found that the students spent for different amount, method and priority depend-ing on their wants and habits. The suggestion for future research can be related to the impact of financial behavior or maybe about financial literacy and management.